ARTIFICIAL INTELLIGENCE AND GLOBAL DIPLOMACY: REDEFINING POWER STRUCTURES IN THE 21ST CENTURY - Unggul Sagena; Khalil Zaman; Shazia Akhtar (Cognitionis Civitatis et Politicae, 2025)
The rapid advancement of Artificial Intelligence (AI) has significantly impacted various sectors, including global diplomacy and international relations. In the 21st century, AI is redefining power structures by influencing decision-making processes, national security strategies, and diplomatic negotiations. However, the extent to which AI reshapes global power dynamics and the implications for traditional diplomacy are not yet fully understood. This research explores how AI technologies are altering the balance of power among nations and international institutions. The study aims to examine the role of AI in reshaping global diplomacy and its potential to redefine power hierarchies in international relations. Specifically, it focuses on analyzing the influence of AI on strategic decision-making, cybersecurity, and the geopolitical landscape. The research also seeks to assess the ethical challenges and opportunities that AI presents in the context of diplomacy. A qualitative research method is used, combining case studies of countries actively integrating AI into their diplomatic strategies and expert interviews with diplomats, policymakers, and AI specialists. Data is analyzed thematically to identify emerging patterns in how AI affects power structures and global governance. The findings indicate that AI is both empowering and disrupting traditional diplomatic practices. Countries with advanced AI capabilities gain strategic advantages, while those lagging behind face increased vulnerabilities. AI also introduces new ethical dilemmas in diplomacy, particularly in decision-making transparency and accountability. In conclusion, AI is redefining global power structures by reshaping diplomatic strategies and altering geopolitical alliances. Future research should focus on addressing the ethical implications and ensuring equitable access to AI technologies across nations to prevent widening global disparities.